Towards a simulation environment for Operating Cycle Analysis of Road Transports - Venbrant, Stefan (My University, 2015)
One of the biggest challengers in today’s vehicle industry is to reduce fuel consumption, reduce emissions and lower energy consumption. There is several ways that the car manufacturers engage these challenges, like downsizing engines, reducing aerodynamic resistance etc. Another way is to investigate how the vehicles are being used and configure them based on that. This means that e.g. a truck intended for city driving could be configured for this already when ordered by the logistic company. For this to occur simulations performed in simulation softwares must be improved and operating cycles used in these simulations has to be more accurate. There are two main aims with this thesis: the first is to investigate and propose two simulation environments that could be used by stockholders interested of performing their own simulations on Volvo vehicles and others. One should be open source software for stockholders who cant afford to buy expensive softwares. The second aim is to be a start-up phase for a larger project called OCEAN [1]. This is conducted as follows: a number of simulation softwares are investigated and two are chosen, these are Simulink and OpenModelica. A standard called FMI (Functional Mock-up Interface) is investigated and later used. FMI allows models to be exchanged between different softwares called S-models meaning that parameters can be changed but the equations behind are hidden. Four simulation combinations of a truck are built in the following combinations and softwares (one model was made in OpenModelica but because of problems in OpenModelica Dymola had to be used instead, see conclusions if more interested): 1. Simulink model built and simulated in Simulink 2. Model modelled in a Modelica tool and simulated in Dymola 3. Simulink model with FMUs generated in a Modelica tool 4. Model modelled in a Modelica tool with FMUs generated in Simulink and simulated in Dymola Result of actual speed v_is, accelerator and brake pedal position, simulation time and fuel consumption are recorded and compared, this to see if a vehicle built in different softwares but with the same parameters give the same result. Conclusions are made and recommendation on softwares and future work is made.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering